Design and Build an E-Commerce Website as a Means of Market Network Development for UMKM MDF Pressing - Maulida, Rizka Laila; Azizah, Azizah -; Malebra, Irawan -; Sulistiyani, Endang - (Admisi dan Bisnis, 2024)
E-commerce websites are recognized as effective long-term marketing tools in the digital realm. Through websites, users can access comprehensive information about products or services. MDF Pressing, a Small and Medium Enterprise (SME) operating in the school supply manufacturing sector, currently conducts its marketing efforts offline by physically visiting or calling schools. This approach poses challenges in reaching a wider market. Furthermore, the business management system of MDF Pressing relies on conventional manual record-keeping in physical notebooks. The objective of this research is to develop an online market presence and facilitate business management by constructing an e-commerce website using the Content Management System WordPress. The website development is undertaken through the Waterfall model of system design. The results of this study demonstrate that sales transactions can now be conducted online, enabling customers to save time and effort by avoiding physical visits. Additionally, the website has been integrated with Instagram and Shopee, and SEO optimization has been successfully implemented. Consequently, information exchange about products has become easily accessible, contributing to the expansion of market outreach. Furthermore, business management has become more convenient, as the website incorporates various features that streamline administrative  tasks.